Ethnobotanical Study of Karo Traditional Ceremony in Wonokitri Village, Tosari District, Pasuruan Regency - Berliana, Mita; Batoro, Jati; Azrianingsih, Rodiyati (Universitas Brawijaya, 2026)
The Karo traditional ceremony is the second biggest celebration after Kasada for the Tengger tribe. Wonokitri Village, Tosari District, Pasuruan Regency, is a village whose people still preserve a series of Karo traditional ceremonies. These activities use various types of plants for offerings, which makes the connection between Karo traditional culture and ethnobotany very close. This study aimed to identify the series of Karo traditional ceremonies and the plants used, the symbolic and philosophical meanings of the plants, to determine the number of plant species utilised with Use Value (UVs) and Index of Cultural Significance (ICS), to measure the perceptions of the Wonokitri community in Karo traditional ceremonies with a Likert scale, and SWOT analysis to develop strategies for the conservation and preservation of plants used in Karo traditional ceremonies. The research was carried out using purposive sampling and the snowball sampling techniques. Data were collected through semi-structured interviews with a total of 108 respondents. The results showed that 19 plant species were used in a series of Karo traditional ceremonies: njenang, takeran, sodoran, sesanti, ojung dance, nyadran, semeninga, and tutupan karo. Musa paradisiaca var. raja had the highest ICS (282) and UVs (0.12) values. Each plant has a symbolic and philosophical meaning, for example, gedhang ayu has the symbolic meaning of honouring. Based on the SWOT analysis, Wonokitri Village possesses greater opportunities than threats. However, internally, it has more weaknesses than strengths. Therefore, it is necessary to develop a cultural preservation strategy as an entry point for environmental education by utilising external support, packaging it in the form of cultural-educational tourism, and involving youth to ensure sustainability.